(untitled) (Journal of Applied Membrane Science & Technology, 2024)
Due to the continuing growth in RO desalination plants and the finite lifespan of the RO membranes, large stocks of the end-of-life (EoL) RO membranes are discarded to landfills. This has become a critical challenge in the RO desalination industry. The overall objective of this study was to validate the possibility of direct reuse of the end-of-life seawater reverse osmosis membranes (EoL SWRO) for brackish water desalination in order to limit the environmental impact of their disposal. This study investigates the membrane performance and characterization of four SWRO modules (EoL-M1, EoL-M2, EoL-M3, and EoL-M4). The hydraulic performance of the old membranes was assessed using 5,000 ppm synthetic (NaCl) brackish water and real brackish water, and was compared with the performance of two commercial membranes, namely brackish water RO membrane (BW30) and nanofiltration membrane (NF90). 84-92% NaCl rejection was achieved by direct reuse of EoL membranes, which was higher than the rejection characteristics obtained using commercial BW30 and NF90 membranes. Removal of common salts represent in natural water sources (Na2SO4, Mg2SO4 and MgCl2) and humic substances was also investigated using EoL membranes. The rejection of Na2SO4, MgSO4 and MgCl2 salt solutions was in the range of (50.0-85.8%) with a highest rejection value was obtained for Na2SO4 and the lowest rejection was observed for MgCl2 solution, while a complete rejection was achieved for humic acid. Salt rejection of real brackish water filtration by the EoL membranes (75-77%) presented NF-like properties (Salt rejection was obtained for NF90 membrane was 77%). Therefore, the potential of reusing EoL SWRO is promising and thus benefit the desalination industry and the environment in Oman.